Porous circuits: Tsai Ming-liang, Zhao Liang, and Wang Bing at the Venice International Film Festival and the interplay between the festival and the art exhibition circuits. Issue 2 (4th May 2019) - Pollacchi, Elena
Abstract: From the perspective of film festival studies and on the basis of my first-hand experience at the Venice Film Festival, this article sheds some light on how the works of Tsai Ming-liang, Zhao Liang, and Wang Bing elucidate the interplay between the art exhibition and film festival circuits. These artist-filmmakers have contributed to and taken advantage of the porosity between the two circuits. Taking the Venice Film Festival as a vantage point of observation, this article discusses how their works have been able to move in and out the festival circuit to reach art exhibition spaces. Against a changing production and exhibition back-drop, they have fruitfully expanded their activities, reached a broader audience and expanded their production and exhibition network. What are the advantages and limitations of such porous systems? What is to be found that facilitates the dissemination of certain works across the two circuits? How do reputation and international prestige – here read as an expansion of Bourdieu's "cultural capital" – translate into more production and exhibition opportunities? This organic discussion by taking into account the changes in the political economy of film production and exhibition in relation to certain aesthetic features, investigates the contrasting ways in which the festival and art circuits provide their own specific framing, produce different modes of meaning-making and result in quite different audience receptions. Furthermore, some observations on the works of the three artist-filmmakers suggest that festivals have progressively included these "festival and gallery films" in their regular programmes despite the challenges they present. This reinforces the idea of a virtuous circuit of increasing crossovers through which, artist-filmmakers capitalize on the reputation and prestige earned in one of the two circuits and invest it in the other. At the same time, film festivals have to take up new challenges, programming works with unconventional features that can be slower paced and of longer duration compared to what a festival audience is used to.